2012
DOI: 10.1016/j.idairyj.2011.10.005
|View full text |Cite
|
Sign up to set email alerts
|

H, C, N and O stable isotope characteristics of alpine forage, milk and cheese

Abstract: a b s t r a c t H, C, N, O stable isotope ratios of forage, milk and the corresponding cheese were analysed to define the isotopic characteristics of two typical mountain cheeses produced in two different terroirs with different types of vegetation. d 13C was shown to be mainly influenced by the presence of C4 plants in animal diet and, in the case of C3 plant-based forage it was below À23& varying according to the site and herbage type. d 15 N is more related to vegetation type and confirmed to be lower than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 41 publications
7
58
0
Order By: Relevance
“…Especially the stable isotope ratio of carbon in milk fat and in the milk protein fraction allows drawing conclusions on the origin and authenticity of milk and dairy products (Bontempo, Lombardi, Paoletti, Ziller, & Camin, 2012;Camin et al, 2012). Furthermore, Molkentin and Giesemann (2007) reported that additional analysis of the a-linolenic acid (C18:3x3) content resulted in significant discrimination between organically and conventionally produced milk.…”
Section: Introductionmentioning
confidence: 99%
“…Especially the stable isotope ratio of carbon in milk fat and in the milk protein fraction allows drawing conclusions on the origin and authenticity of milk and dairy products (Bontempo, Lombardi, Paoletti, Ziller, & Camin, 2012;Camin et al, 2012). Furthermore, Molkentin and Giesemann (2007) reported that additional analysis of the a-linolenic acid (C18:3x3) content resulted in significant discrimination between organically and conventionally produced milk.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that stable isotopes (H and O) can differentiate the sources of agrofood products such as milk and cheese (Bontempo et al, 2011;Bontempo, Lombardi, Paoletti, Ziller, & Camin, 2012;Crittenden et al, 2007;Kornexl, Werner, Rossmann, & Schmidt, 1997;Manca et al, 2001;Rossmann, 2001;Rossmann, Kornexl, Versini, Pichlmayer, & Lamprecht, 1998;Silva et al, 2014). Radiogenic isotopes such as strontium have also been used to discriminate the sources of milk and cheese (Bontempo et al, 2011;Crittenden et al, 2007;Fortunato et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Values within the same column with different lowercase letters are significantly different at P<0.01 and classified on the basis of the content of δ 13 C and δ 15 N. The results they found were quite consistent with our results, which was that milk samples from four different regions, Australia and New Zealand, Germany and France, the USA, and China, could be easily discriminated and classified by δ 13 C and δ 15 N values. As for oxygen isotope compositions, as the 18 O content of local water was related to the climatic and geographical features of an area (temperature, humidity, rainfall, distance from the sea, altitude and latitude), milk water δ 18 O could distinguish between milk produced in different areas (Bontempo et al 2012;Chesson et al 2010). As can be seen in Table 1, the mean δ 18 O values of milk water originated from Australia and New Zealand, Germany and France, the USA, and China were −11.102, −10.460, −22.396, and −13.060‰, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The stable isotope ratios of which may change according to the tissue or class of compounds considered (e.g., lipids). As the isotopic ratios of diet constituents and water are related to local environment, isotope ratio analysis has recently been used to discriminate between milk produced in different areas, with different dietary regimes and production systems (Bontempo et al 2011(Bontempo et al , 2012Chesson et al 2010;Crittenden et al 2007;Engel et al 2007). For example, C and N isotope ratios in living creatures can be related to those found in nature.…”
Section: Introductionmentioning
confidence: 99%